2012
DOI: 10.1002/ppul.22562
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of thoracic CT to diagnose tuberculosis disease in patients younger than 4 years of age

Abstract: In children younger than 4-year old with positive TST and normal CXR, it would be advisable to perform a TCT since the findings could change the diagnosis from TBI to TB disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
3
19
0
2
Order By: Relevance
“…A recent study analyzed the usefulness of CT in the diagnosis of TB in a TB outbreak that affected 28 children younger than 4 years in a nursery in Spain [54]. Fourteen of the children had normal chest X-ray but 12 of them (8 without any clinical symptom) presented adenopathies >10 mm or infiltrates on CT.…”
Section: Ct In Children With Tuberculosis Infection and With No Apparmentioning
confidence: 99%
“…A recent study analyzed the usefulness of CT in the diagnosis of TB in a TB outbreak that affected 28 children younger than 4 years in a nursery in Spain [54]. Fourteen of the children had normal chest X-ray but 12 of them (8 without any clinical symptom) presented adenopathies >10 mm or infiltrates on CT.…”
Section: Ct In Children With Tuberculosis Infection and With No Apparmentioning
confidence: 99%
“…These results are similar to those obtained by other authors. [29][30][31][32] Regarding the lymph nodes, the necrotic aspect, with peripheral contrast enhancement and hypodense center, was statistically significant associated with changes in lung parenchyma, bronchial compression, and positive culture. This data support the idea that this type of lymphadenopathy is typical of TD and reflect its activity.…”
Section: Delacourt Et Al 21 Performed Chest Ct In 15 Children With Nomentioning
confidence: 96%
“…This conclusion is the same as Garrido et al observed in their work. 30 Since in these cases there is an increased risk of progression and complications of TD, CT would have on them the clearest indication. Another possibility is chemoprophylaxis in this group with two drugs.…”
Section: Delacourt Et Al 21 Performed Chest Ct In 15 Children With Nomentioning
confidence: 99%
“…Hiler veya mediastinal lenf nodu büyümesi TB'li hastaların BT incelemelerinde en sık karşılaşılan bulgudur fakat reaktivasyon TB'de yaygın değildir (28). Bazı yazarlar, patolojik lenf nodlarının 5 ile 10 mm arasında olduğunu diğerleri ise 10 mm'den daha büyük olanların patolojik olduğunu vurgulamıştır (29,30). Bu çalışmada tBT'de 10 mm'den daha büyük lenfadenopatiler patolojik lenf nodu olarak kabul edildi.…”
Section: İstatistiksel Analizunclassified